2008
DOI: 10.1577/t07-068.1
|View full text |Cite
|
Sign up to set email alerts
|

How Systematic Age Underestimation Can Impede Understanding of Fish Population Dynamics: Lessons Learned from a Lake Superior Cisco Stock

Abstract: Systematic underestimation of fish age can impede understanding of recruitment variability and adaptive strategies (like longevity) and can bias estimates of survivorship. We suspected that previous estimates of annual survival (S; range = 0.20‐0.44) for Lake Superior ciscoes Coregonus artedi developed from scale ages were biased low. To test this hypothesis, we estimated the total instantaneous mortality rate of adult ciscoes from the Thunder Bay, Ontario, stock by use of cohort‐based catch curves developed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 29 publications
2
67
0
Order By: Relevance
“…This range of biomass levels was similar to that obtained for the same regions by Mason et al (2005) in 1997 (7.9-24.4 kg ha −1 ). Obtaining comparable estimates to Mason et al (2005) is not overly surprising given (1) the dominant fauna by weight (cisco) can live up to age-21 in Lake Superior, and (2) strong year-classes of this species recruited in Lake Superior during 1998 and 2003 (Yule et al, 2008). estimated biomass of omul in Lake Baikal over differ- Rudstam et al (1987) also had higher cisco biomass levels than we measured (Trout Lake 51 kg ha −1 and Lake Mendota 223 kg ha −1 ), while one was lower (Big Muskellunge 2.4 kg ha −1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This range of biomass levels was similar to that obtained for the same regions by Mason et al (2005) in 1997 (7.9-24.4 kg ha −1 ). Obtaining comparable estimates to Mason et al (2005) is not overly surprising given (1) the dominant fauna by weight (cisco) can live up to age-21 in Lake Superior, and (2) strong year-classes of this species recruited in Lake Superior during 1998 and 2003 (Yule et al, 2008). estimated biomass of omul in Lake Baikal over differ- Rudstam et al (1987) also had higher cisco biomass levels than we measured (Trout Lake 51 kg ha −1 and Lake Mendota 223 kg ha −1 ), while one was lower (Big Muskellunge 2.4 kg ha −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Biomass of spawningsize cisco, however, is best estimated during November when pre-spawning aggregations form. Yule et al (2008) demonstrated that November acoustic and midwater-trawl surveys could be combined with commercial catch data to estimate exploitation levels at a given locale, provided that the fishery-independent survey work occurs after the bulk of spawners have returned to that site. However, given the time needed to process the survey results, the data cannot be used to set harvest quotas until the next fishing season.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate age data coupled with other fisheries metrics can be used to estimate growth, mortality rates, population structure, and change in species abundance, biomass, and yield. However, inaccurate age estimation can lead to gross errors in stock metrics (e.g., recruitment, growth, and mortality) and adversely affect management strategies (Mills and Beamish 1980;Beamish and McFarlane 1983;Lai and Gunderson 1987;Leaman and Nagtegaal 1987;Tyler et al 1989;Reeves 2003;Yule et al 2008). Therefore, it is crucial that fisheries managers and biologists use the best available methods to estimate age.…”
Section: Introductionmentioning
confidence: 99%
“…If age information is unreliable, population models used for prediction of population dynamics may result in the implementation of liberal catch limits and the potential for overharvest. For instance, Yule et al (2008) suggested non-reliable ageing structures resulted in faulty age information and inaccurate harvest models with the subsequent over-harvest and depletion of cicso (Coregonus artedi, Salmonidae) population abundances and a collapse of the fishery in Lake Superior, USA. As such, fisheries professionals need reliable information on the true ages of organisms of interest.…”
Section: Introductionmentioning
confidence: 99%